Kedudukan Akta Notaris Sebagai Alat Bukti dalam Proses Pemeriksaan Perkara Pidana - Tri Yanty Sukanty Arkiang (KEADILAN PROGRESIF, 2011)
The position of notary as evidence in criminal cases is the same examination with thetools that the other evidence. This is because the criminal deed does not have perfectpower. So the judge does not have to believe that the contents of the notarial deedare correct. Thus the value of that evidence sought to be free because the law ofcriminal procedure is the accuracy of the consequences and the judge is free to use oroverride a letter of evidence.The implementation of the decision-deed performed bythe investigator for the benefit of the judicial process investigator, prosecutor, orjudge with the approval of the Regional Board. Trustees are authorized to take photocopies minuta deed and/or letters attached to the deed minuta, or protocols in storagenotary and call notary tobe present in the examination relating to the deed made orprotocols that are instorage notary.